Impact of clinical audits on cesarean section rate in a Spanish hospital: Analysis of 6 year data according to the Robson classification. (November 2020) - Pinto, Patricia; Crispín-Milart, Patricia H.; Rojo, Elena; Adiego, Begoña
Highlights: Clinical audit has shown a very positive impact in lowering C section rates. TGCS seems to be the most appropriate classification to compare Cs rates nowadays. In our population, groups 1, 2a and 5 are the main contributors to our Cs rate. The avoidance of elective procedures might decrease primary Cs sections and IOL. Counselling for trial of labor after cesarean section might be another target. Abstract: Objectives: The aim of this study is to analyze the impact of the introduction of an internal clinical audit on the cesarean section (CS) rate, evaluated according to the Robson Ten Group Classification System (TGCS), and to identify the main contributors to the overall CS rate in order to plan further interventions. Study Design: In 2014, an internal clinic audit committee was established in our center. Modifications of clinical management protocols were also implemented. A retrospective review of clinical records was conducted and pre-audit (2011−2014) results were compared against audit (2015−2018) results. Patients were clustered according to the Robson TGCS and the analyzed outcomes were CS rate and maternal and neonatal results. Results: Between January 2011 and December 2018, 12, 766 women gave birth at our institution among which 2, 281 CS were analyzed. After the establishment of the clinical audit, the overall CS rate decreased from 20.27% to 14.82 % (p < 0.01). The major contribution to the overall CS rate in both periods were made by Group 2a (nulliparous with a single cephalic pregnancy at term who underwent labor induction: 4.86 % of all cases), followed by Group 5 (patients with a previous C-section: 3.26 %) and Group 1 (nulliparous with a single cephalic pregnancy at term with spontaneous labor: 2.39 %), representing 59.6 % of all CS. The group that showed the greatest reduction to the overall Cs rate was Group 2 (5.77 % vs 3.96 %, OR 1.48 (p < 0.01). No differences in perinatal and maternal results were found between preaudit and audit group. Conclusion: Audit, feedback, and modification of clinical management protocols may be effective in changing clinical practice and reducing CS rates without worsening maternal and neonatal morbimortality. Robson TGCS allowed us to identify which groups had the greatest impact on CS rate in order to establish new strategies that may lead us to optimize the use of this intervention. It seems that efforts to reduce the overall CS rate should be directed on increasing vaginal birth after CS and reducing CS rates in nulliparous women with single cephalic full-term pregnancy.